MODEL PEMETAAN POTENSI DAERAH MENUJU KEMANDIRIAN - Zumrotul Fitriyah; Syamsul Huda (Trunojoyo University of Madura, 2017)
Dengan munculnya UU No .22 tahun 1999 yang mengatur perlimpahan wewenang dan tanggung jawab dari pemerintah pusat kepada pemerintah daerah serta UUNo.25 tahun 1999 yang mengatur pierimbangan keuangan antara pusat dan daerah khususnya di Kabupaten //kota di Jawa Timur dengan menggembangkan sumber daya lokal dan mengurangi ketergantungan dari pusat Penelitian ini bertujuan untuk mengetahui kemandirian daerah Kabupaten/ Kota di Jatim Analisa yang digunakan adalah analisa kualitatif, yaitu analisa yang sifatnya menjelaskan secara uraian atau dalam bentuk kalimat-kalimat dan analisa kuantitatif yaitu analisa dengan menggunakan rumus-rumus dan analisa pasti. Analisa kuantitatif meliputi analisa derajat desentralisasi fiskal untu mengetahui tingkat kemandirian daerah dan potensi ekonomi sektoral di Kabupaten /Kota di Jawa Timur sehingga dapat mengetahui tingkat kemandirian fiskal dan potensi Ekonomi daerah. Hasil penelitian diharapkan dapat digunakan mengethui pola hubungan yang terjadi antara pemerintah pusat dengan pemerintah di kabupaten /Kota di Jawa Timur serta formula kebijakan yang tepat untuk pengembangan ekonomi ke depan. With the advent of Law No .22 years 1999 set an authority and responsibility from central government to local government and UUNo.25 1999 governing financial between the center and regions, especially in the District city in East Java n local resources and reduce dependence of the center. This study aims to determine the independence of the Regency / City in East Java analysis used is qualitative analysis, the analysis that are explained in the description or in the form of sentences This study aims to determine the independence of the Regency / City in East Java analysis used is qualitative analysis, the analysis that are explained in the description or in the form of sentences and quantitative analysis, namely analysis using formulas and definite analysis. Quantitative analysis includes the analysis of the degree of fiscal decentralization determine the level of independence of regional and sectoral economic potential in the District East Java so that it can determine the level of fiscal independence and economic potential of the region. Results are expected to be used i pattern of the relationship between the central government and the government in the district / city in East Java as well as the formula right policy for future economic development. From this research it is known that the city of Surabaya has a degree of fiscal autonomy for PAD at 48% of revenue while the region Gresik on the degree of fiscal autonomy degree Enough and Sidoarjo district in degrees, please. There are 32 regions in the East dijawa degree of fiscal independence of each very less independent, meaning of Balance Funds as well as from centers of poropinsi